Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
+) \(\left(x-3\right)^2=16\)
\(\Rightarrow\orbr{\begin{cases}\left(x-3\right)^2=4^2\\\left(x-3\right)^2=\left(-4\right)^2\end{cases}\Rightarrow}\orbr{\begin{cases}x-3=4\\x-3=-4\end{cases}}\Rightarrow\orbr{\begin{cases}x=7\\x=-1\end{cases}}\)
Vậy x = 7 hoặc x = -1
+) \(\left(1-3x\right)^3=-64\)
\(\Rightarrow\left(1-3x\right)^3=\left(-4\right)^3\)
\(\Rightarrow1-3x=-4\)
\(\Rightarrow3x=1+4\)
\(\Rightarrow3x=5\)
\(\Rightarrow x=5:3\)
\(\Rightarrow x=\frac{5}{3}\)
Vậy \(x=\frac{5}{3}\)
+) \(x^{13}=27.x^{10}\)
\(\Rightarrow x^{13}:x^{10}=27\)
\(\Rightarrow x^3=27\)
\(\Rightarrow x^3=3^3\)
\(\Rightarrow x=3\)
Vậy x = 3
+) \(\left(4x-1\right)^2=\left(1-4x\right)^4\)
\(\Rightarrow\left(4x-1\right)^2=\left(4x-1\right)^4\)
\(\Rightarrow\left(4x-1\right)^2-\left(4x-1\right)^4=0\)
\(\Rightarrow\left(4x-1\right)^2\left[1-\left(4x-1\right)^2\right]=0\)
\(\Rightarrow\orbr{\begin{cases}\left(4x-1\right)^2=0\\1-\left(4x-1\right)^2=0\end{cases}}\Rightarrow\orbr{\begin{cases}\left(4x-1\right)^2=0\\\left(4x-1\right)^2=1\end{cases}}\)
TH 1 : \(\left(4x-1\right)^2=0\Rightarrow4x-1=0\Rightarrow4x=1\Rightarrow x=\frac{1}{4}\)
TH 2 : \(\left(4x-1\right)^2=1\Rightarrow\orbr{\begin{cases}4x-1=1\\4x-1=-1\end{cases}}\Rightarrow\orbr{\begin{cases}4x=2\\4x=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{1}{2}\\x=0\end{cases}}\)
Vậy \(x\in\left\{\frac{1}{4};\frac{1}{2};0\right\}\)
_Chúc bạn học tốt_
a, (x-3)^2 = 16
=> (x-3)^2=4^2
=> x-3=4
=> x= 4+3
=> x = 7 .Vậy x =7
b,(1-3x)^3 = 64
=> ( 1-3x)^3 = 4^3
=> 1-3x = 4
=> 3x = 1-4
=> 3x = -3
=> x = -1 . Vậy x = -1
c, x^13 = 27.x^10
=> x^13 : x^10 = 27
=> x^3 = 3^3
=> x = 3 . Vậy x = 3
a) 1020 và 9010
ta có: 1020 = (102)10 = 10010
vì 100 > 90 nên 10010 > 9010
vậy 1020 > 9010
b) tương tự nhé
ok mk nhé!!! 5656757567687686712676576568768763575475437445756725676568
\(\frac{\left(-4\right)^x}{64}=-16\)
\(\Leftrightarrow\left(-4\right)^x=64.16\)
\(\Leftrightarrow\left(-4\right)^x=1024\)
\(\Leftrightarrow4^x=1024\)
\(\Leftrightarrow4^x=4^5\)
\(\Rightarrow x=5\)
\(64^x.16^x=256^{12}:1024\)
\(\Rightarrow\) \(\left(4^3\right)^x.\left(4^2\right)^x=\left(4^4\right)^{12}:4^5\)
\(\Rightarrow\) \(4^{3x}.4^{2x}=4^{48}:4^5\)
\(\Rightarrow\) \(4^{3x+2x}=4^{43}\)
\(\Rightarrow\) \(3x+2x=43\)
\(\Rightarrow\) \(\left(3+2\right)x=43\)
\(\Rightarrow\) \(5x=43\)
\(\Rightarrow\) \(x=\frac{43}{5}\)
a) \(64^x:16^x=256\)
\(\Rightarrow\left(2^6\right)^x:\left(2^4\right)^x=2^8\)
\(\Rightarrow2^{6x}:2^{4x}=2^8\)
\(\Rightarrow2^{6x-4x}=2^8\)
\(\Rightarrow2^{2x}=2^8\)
\(\Rightarrow2x=8\)
\(\Rightarrow x=4\)
b) \(\dfrac{-2401}{7^x}=-7\)
\(\Rightarrow\dfrac{-7^4}{7^x}=-7\)
\(\Rightarrow-7^{4-x}=-7\)
\(\Rightarrow7^{4-x}=7\)
\(\Rightarrow4-x=1\)
\(\Rightarrow x=4-1\)
\(\Rightarrow x=3\)
c) \(\dfrac{64}{\left(-4\right)^x}=-256\)
\(\Rightarrow\left(-4\right)^x=\dfrac{64}{-256}\)
\(\Rightarrow\left(-4\right)^x=-4\)
\(\Rightarrow\left(-4\right)^x=\left(-4\right)^1\)
\(\Rightarrow x=1\)
\(a) 64^x:16^x=256\\\Rightarrow (64:16)^x=256\\\Rightarrow 4^x=4^4\\\Rightarrow x=4\\---\)
\(b,\dfrac{-2401}{7^x}=-7\)
\(\Rightarrow7^x=-2401:\left(-7\right)\)
\(\Rightarrow7^x=343\)
\(\Rightarrow7^x=7^3\)
\(\Rightarrow x=3\)
\(c,\dfrac{64}{\left(-4\right)^x}=-256\)
\(\Rightarrow\left(-4\right)^x=64:\left(-256\right)\)
\(\Rightarrow\left(-4\right)^x=-\dfrac{1}{4}\)
\(\Rightarrow\left(-4\right)^x=\left(-4\right)^{-1}\)
\(\Rightarrow x=-1\)
#\(Toru\)
16x = 6410
16x = 1152921504606846976
=> 16x = x = 15.
16x = 6410
(42)x = (43)10
42x = 430
2x = 30
x = 30 : 2
x = 15